Aire Gene Influences the Length of the 3′ UTR of mRNAs in Medullary Thymic Epithelial Cells - Oliveira, Ernna H.; Assis, Amanda F.; Speck-Hernandez, Cesar A.; Duarte, Max Jordan; Passos, Geraldo A. (Frontiers in Immunology, 2020)
Together in a population, medullary thymic epithelial cells (mTECs) transcribe near 80% its genome and still maintain their morpho-functional characteristics. The implication of this uncommon transcriptional activity is essentially immunologic, i.e., a large set of the expressed genes encode peripheral tissue antigens (PTAs) that guarantees self-representation in the thymus. Aire gene is a key upstream transcriptional controller of this process modulating the expression of a set of PTA and non-PTA mRNAs as well as miRNAs, which are referred to as Aire-dependent. Even miRNAs exerting posttranscriptional control of mRNAs in mTECs, the composition of miRNA-mRNA networks may differ. Under reduction in Aire expression, interaction networks exhibited greater miRNA diversity controlling mRNAs. Variations in the number of 3'UTR binding sites of Aire-dependent mRNAs may represent a crucial factor that influence the miRNA interaction. To test this hypothesis, we analyzed the length of 3' UTRs of a large set of Aire-dependent mRNAs whose data were obtained from RNA-Seq of mTECs isolated of wild type or Aire-knockout (KO) mice. We identified 193 differentially expressed mRNAs between these samples that comprise two sets that were focused in this study, one that encode PTAs and another non-PTAs including transcription regulators. In the absence of Aire (KO), most of these mRNAs featured an increase in the length of their 3' UTRs originating additional miRNA binding sites and consequently further miRNA controllers. Lack of Aire might favoring the downregulation of key PTA and transcription regulators mRNAs via miRNA control, unbalancing thus the overall transcriptional activity in mTECs and consequently the self-representation in the thymus.